Movers of the Functional Lethargy and the proposal of Sustainable Human Development in the Kurdistan Region - األسخاذ اىدنخٔر ٌطٍد ضرةٖ ضسَ (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The importance of talking about functional lethargy comes from the fact that this lethargy is the most important indicator of the performance statement Therefore, this research seeks to clarify this relationship by talking about the forms of Functional lethargy and its movers, which are: 1- Administrative lethargy 2- Professional lethargy 3 - Technical lethargy 4 – Skills lethargy 5 – Sickness lethargy 6. Social lethargy 7- Moral lethargy These forms produce a range of implications for administrative and organizational performance: 1. The lack of management systems; the practice of administrative functions has become confused and unprofessional 2. Failure of career empowerment; lack of professional practice leads to skills decline 3. Negative regulatory dependence; management neglect of values and rejection of employee attitudes 4 - The spread of administrative corruption; administrative corruption has become a phenomenon and culture cannot be removed The research recommends the preparation and implementation of the following: 1. Human Resources Strategy (Strategic Plan, Operational Plan) 2. Job description. 3. Human budget system (grades, staffing, selection, and recruitment) 4. Job Appraisal System (employee performance appraisal, workforce assessment) 5. The system of measuring employee attitudes (measuring satisfaction, loyalty, turnover / stability) 6. Human investment system (mobility, optimal employment of human resource) 7. Functional Empowerment System (Job Performance, Training, Authorization, and Motivation) and (Incentives, bonuses, compensation, social security and retirement).